Evaluating the Chile Solidario program: results using the Chile Solidario panel and the administrative databases - Hoces de la Guardia, Fernando; Hojman, Andrés; Larrañaga, Osvaldo (Estudios de Economía, 2016)
This paper presents the results of a three-year evaluation performed on the first cohorts of Chile Solidario, the most important anti-poverty program in Chile. The paper presents a description of the program, emphasizing the mechanism by which people were admitted into the program. We then propose evaluation strategies and discuss their validity. The final evaluation is conducted using a Matching estimator, and we discuss the principles surrounding the potential for this to be a valid evaluation method. The initial results using the Chile Solidario Panel suggest that the program had positive effects on psychosocial welfare and on take-up of subsidies and social programs. However, it is not possible to obtain reliable results due to data shortcomings, particularly the lack of baseline data. In order to solve the problem, we generated a database using six years of administrative data, including around 1,000,000 family records per year. A method for overcoming the treatment substitution problem is discussed and implemented. Results are much more robust than those of the Chile Solidario Panel and show small, but clearly positive effects for several variables, especially the number of workers in the family, the percentage of workers in the family and the employment of the head of the family.